Pola Penggunaan Aplikasi Transportasi Online di Kalangan Asisten Rumah Tangga - Hidayat, Mochamad Taufiq; Hesti, Sri; Nurhikmah, Nurhikmah (Universitas Mercu Buana, 2022)
This study aims to reveal and map patterns or models of information search for household assistants as consumers of users of online transportation services. Using a case study approach is expected to reveal consumer behavior patterns and information search models relating to new economic products that can be developed for new professions in Indonesia.The results showed there were differences in ART in the search for information, for personal interests such as work leave, going with friends to the Mall, delivering to the station, ordering food and there were some who used it to support their work. Usually they prefer cash payments, and take advantage of discount promos.In the study also found three behavioral patterns in ART, namely (1) the usual personal pattern of informants using applications for personal needs. (2) Work Support Patterns on ART that they usually use online transportation applications to support their work, and (3) Social Patterns, where use is intended to help other ART members who cannot use the application.